Coal Quality Analysis Based on Proximate and Ultimate Test Results in Massenreng Pulu Village, Lamuru District, Bone Regency - Bakri, Suriyanto; Jefri, J; Widodo, Sri (Journal of Geology and Exploration, 2022)
Coal is one of the minerals that has an important role in the mining industry in Indonesia. Massenreng Pulu Village, Lamuru District, Bone Regency, South Sulawesi Province is an area that has coal resources, the quality of coal in that area needs to be known. The quality of coal has a very important role in the utilization of coal. Coal quality parameters will affect the intended use of coal. The purpose of this study was to analyze the quality of coal based on the proximate and ultimate analysis tests. The sampling method was channel sampling, samples from the field were then brought to the laboratory for preparation and analysis proximately and ultimately. The results of the proximate analysis of coal samples contained an average moisture content of 15.75% ar, ash content of 3.48% ar, volatile matter of 42.35% ar and fixed carbon of 37.91% ar while the results of the ultimate analysis of coal samples contained an average of 66.52% carbon. wt, 4.6% wt hydrogen, 0.93% wt nitrogen and 23.05 wt oxygen. Based on the ash content, if classified according to The UNECE 1998 classification of in seam coals, it can be seen that the rank of coal in the study area is classified as high grade coal.